Prevalence of polypharmacy and associated adverse outcomes and risk factors among children with asthma in the USA: a cross-sectional study. Issue 10 (13th October 2022) - Xie, Luyu; Gelfand, Andrew; Murphy, Caitlin C; Mathew, M Sunil; Atem, Folefac; Delclos, George L; Messiah, Sarah
Abstract : Objective: To estimate the prevalence of polypharmacy, identify risk factors and examine related adverse outcomes in the US children with asthma. Design, setting and participants: This population-based, cross-sectional study included 1776 children with asthma from the 2011–2020 National Health and Nutrition Examination Surveys. Exposures: Polypharmacy is defined as taking ≥2 medications concurrently for ≥1 day over the past 30 days. Main outcomes and measures: (1) Weighted prevalence estimates of polypharmacy in children with asthma; (2) asthma attacks and emergency department (ED) visits. Results: The estimated prevalence of polypharmacy in the US children with asthma was 33.49% (95% CI 31.81% to 35.17%). 15.53% (95% CI 14.31% to 16.75%), 12.63% (95% CI 11.37% to 13.88%) and 5.33% (95% CI) of participants were taking 2, 3–4, and 5 prescription medications, respectively. In addition to asthma medications, the most common sources of polypharmacy included antihistamines (20.17%, 95% CI 16.07% to 24.28%), glucocorticoids (16.67%, 95% 12.57% to 20.78%), and anti-infectives (14.28%, 95% CI 10.29 to 18.28). Risk factors for the increased number of medications included age 5–11 years old (vs 1–4 years: adjusted incidence rate ratio (aIRR) 1.38, 95% CI 1.10 to 1.72), fair-to-poor health (vs excellent or very good: aIRR 1.42, 95% CI 1.05 to 1.92), or ≥6 healthcare utilisation encounters over the last year (vs 0–5 encounters: aIRR 1.45, 95% CI 1.26 to 1.66). Polypharmacy increased the odds of an asthma attack (adjusted OR (aOR) 2.80, 95% CI 1.99 to 3.93) and ED visit (aOR 2.41, 95%1.59–3.63) after adjusting for demographics, insurance and health status. Conclusions: Every one in three US children with asthma experienced polypharmacy. Although it may reflect the treatment guidelines that various asthma medications are needed for maintenance therapy, our results suggested that polypharmacy increased the odds of asthma attacks or ED visits. This may be due to the concurrent use with other non-asthma medications indicating that there is an opportunity to improve medication management in children with asthma.